Timely identification of patients in need of palliative care using the Double Surprise Question: A prospective study on outpatients with cancer. (March 2021) - Ermers, Daisy JM; Kuip, Evelien JM; Veldhoven, CMM; Schers, Henk J; Perry, Marieke; Bronkhorst, Ewald M; Vissers, Kris CP; Engels, Yvonne
Background: The Surprise Question (" Would I be surprised if this patient were to die within the next 12 months?" ) is widely used to identify palliative patients, though with low predictive value. To improve timely identification of palliative care needs, we propose an additional Surprise Question (" Would I be surprised if this patient is still alive after 12 months?" ) if the original Surprise Question is answered with "no." The combination of the two questions is called the Double Surprise Question. Aim: To examine the prognostic accuracy of the Double Surprise Question in outpatients with cancer. Design: A prospective study. Participants: Twelve medical oncologists completed the Double Surprise Question for 379 patients. Results: In group 1 (original Surprise Question "yes": surprised if dead) 92.1% (176/191) of the patients were still alive after 1 year, in group 2a (original and additional Surprise Question "no": not surprised if dead and not surprised if alive) 60.0% (63/105), and in group 2b (original Surprise Question "no, " additional Surprise Question "yes": surprised if alive) 26.5% (22/83) ( p < 0.0001). The positive predictive value increased by using the Double Surprise Question; 74% (61/83) vs 55% (103/188). Anticipatory palliative care provision and Advance Care Planning items were most often documented in group 2b. Conclusions: The Double Surprise Question is a promising tool to more accurately identify outpatients with cancer at risk of dying within 1 year, and therefore, those in need of palliative care. Studies should reveal whether the implementation of the Double Surprise Question leads to more timely palliative care.